Stage lighting the technicians' guide : an on-the-job reference tool - Mort, Skip (Bloomsbury Methuen Drama, 2015)
"This practical guide covers all aspects of stage lighting, equipment, special effects lighting design and features the work of current lighting designers. The online video resources show the practical use of equipment and different lighting technique and effects."--book cover.